A Minimum Wage can be Welfare-Improving and Employment-Enhancing - Robin Boadway; Katherine Cuff (Queen's University, Department of Economics, 1999)
We examine whether minimum wages can fulfill a useful role as part of an optimal nonlinear income tax scheme. In this setting, governments cannot observe household abilities, only their incomes. Redistributing according to income, the government is constrained by a set of incentive constraints. Firms, on the other hand, are able to identify abilities of workers. To exploit that, the government imposes a minimum wage. This will preclude firms from offering a job to anyone below the minimum wage. The use of the minimum wage policy combined with the institutional features of typical welfare systems allows the incentive constraints to be severed at the ability level associated with the minimum wage. If such a scheme can be enforced, the government can increase the amount of redistribution from those working to those not working. Moreover, the optimal minimum wage may actually lower the number of unemployed.
Keywords: H21; H23; J38; 330; Minimum Wage; Optimal Income Tax; Unemployment